(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVES: The aim of this study was to evaluate the intrapulpal temperature variation after bleaching treatment with 35% hydrogen peroxide using different sources of activation. MATERIAL AND METHODS: Twenty-four human teeth were sectioned in the mesiodistal direction providing 48 specimens, and were divided into 4 groups (n=12): (G1) Control - Bleaching gel without light activation, (G2) Bleaching gel + halogen light, (G3) Bleaching gel + LED, (G4) Bleaching gel + Nd:YAG Laser. The temperatures were recorded using a digital thermometer at 4 time points: before bleaching gel application, 1 min after bleaching gel application, during activation of the bleaching gel, and after the bleaching agent turned from a dark-red into a clear gel. Data were analyzed statistically by the Dunnet's test, ANOVA and Tukey's test (a=0.05). RESULTS: The mean intrapulpal temperature values (ºC) in the groups were: G1: 0.617 ± 0.41; G2: 1.800 ± 0.68; G3: 0.975 ± 0.51; and G4: 4.325 ± 1.09. The mean maximum temperature variation (MTV) values were: 1.5ºC (G1), 2.9ºC (G2), 1.7ºC (G3) and 6.9ºC (G4). When comparing the experimental groups to the control group, G3 was not statistically different from G1 (p>;0.05), but G2 and G4 presented significantly higher (p